Women's empowerment across the life cycle and generations: Evidence from Sub-Saharan Africa - (:unkn) unknown (My University, 2017)
Does female empowerment evolve over the life cycle, and has it changed across generations? We use data from the Demographic and Health Surveys covering a sample of about 191,000 adult women to evaluate the age, period and cohort effect regarding individual attitudes to marital violence. Pseudopaneldata are constructed from repeated cross-sections from five African countries in the 2000s. The estimates show that, over the life cycle, women tend to think that marital violence is less and less justifiable, and that younger cohorts are less likely than older cohorts to view marital violence as justifiable, even controlling for education. In the full age-period-cohort decomposition, the age andperiod effects are the most important. Age effects are driven by changes in labor-force status, household composition and parenthood.
Keywords: African Research